Building 'Implicit Partnerships'? Financial Long Term Care Entitlements in Europe - Joan Costa-Font; Valentina Zigante (London School of Economics and Political Science (LSE), European Institute, 2017)
The public funding of long-term care (LTC) programs to support the frail elderly is still underdeveloped compared to other areas of social protection for old age. In Europe, any moves to broaden entitlements to LTC are impeded by increasing demand for care coinciding with constrained public finances. We examine a set of conditions that facilitate modifications to the financial entitlement to LTC and elaborate the concept of 'implicit partnerships': an implicit (or 'silent') agreement, encompassing the financial co-participation of public funders and the time and/or financial resources of users and their families. We argue that the successful building of 'implicit partnerships' opens the door to potential reform of financial entitlements, either through 'user partnerships' relying on users' co-payments, or 'caregiver partnerships' relying on informal care provision. We examine entitlements over time in seven European countries; the EU-5, the Netherlands and Sweden. Furthermore, we show that public attitudes towards financing and provision of LTC support the country specific financial entitlements and the type of implicit partnership we identify.
Keywords: 330; implicit partnership; partial insurance; cost sharing; long-term care; financial sustainability; family; Europe